IMPROVING SURGICAL TREATMENT OF ESOPHAGAL-GASTRIC BLEEDING IN LIVER CIRRHOSIS - Urokov , Shukhrat; Salomov, Nodir; Khamroev , Khudoyshukur (Medical science of Uzbekistan, 2023)
Relevance. Liver cirrhosis (LC) affects the function of the gastrointestinal tract and is associated with hemodynamic abnormalities in the portal system. The pathological processes that occur in the duodenum and stomach are influenced by reciprocal humoral effects and strong functional links between the liver and the organs of the gastrointestinal system. Some causes of bleeding from the upper gastrointestinal tract, their pathogenesis and mechanisms of occurrence are discussed above. Apparently, it is known that the cause of bleeding from the upper gastrointestinal tract is not only pathological changes in the mucous membrane, but also diffuse changes in the liver. There is a lot of information about ulcers (acute and chronic), erosive gastritis, the mechanism of bleeding from PG, clinical course, but information based on scientific research about the combined course of this pathological process is rare. No information about this pathological process, which is one of the pressing problems of medicine, was found in the literature we examined. To date, more than 200 methods of surgical intervention have been proposed, which is explained by the extreme complexity of the problem, the variety of clinical manifestations of the disease and the lack of absolutely reliable methods of surgical treatment. Purpose. Improving the results of surgical tactics in patients with ulcer bleeding combined with liver cirrhosis by choosing the most optimal methods of diagnostic and treatment tactics Material and methods. Considering cirrhosis in combination with duodenal and gastrointestinal ulcers, we examined the results of treatment of 83 patients with bleeding from pg. The age of the patients ranged from 25 to 79 years. The majority of patients (71.1%) with this pathology are of working age (40-60 years). Men made up 67.5% of the population and women 32.5%. The source of bleeding was arrosion of varicose veins (bpb) of the esophagus and gastric cardia in 41 patients (49.4%); gastric and duodenal ulcers in 31 patients (37.3%); in eight of these patients, the source of bleeding was giant gastric and duodenal ulcers; in 11 patients (13.3%) both bpb and gastric and duodenal ulcers were observed simultaneously. Results. Of the 83 patients who underwent surgical treatment, 71 (85.5%) had bleeding from gastric and duodenal ulcers, 24 from arrozed BPB of the esophagus and stomach, and 11 patients had bleeding from both sources at the same time, which led to the need for suturing the BPB of the esophagus, stomach, and duodenum ulcers. 39 (54.9%) unwell patients underwent urgent and urgent surgery (table). B 24 (33.8%) patients had emergency surgery between two hours and one day, during the peak of their bleeding (between two and six hours — 18 ill Eleven patients had bleeding ulcers and eleven had two sources of bleeding (from BPBP and F) at 4–20 hours. Of them, 15 patients (up to 2-3 days) or 21.1% had recurrence bleeding at 4 sick, indicating the need for emergency operational measures. In 32 (45.1%) patients with stable hemostasis.